A Review on Analysis of Anti-Microbial Drugs in Biological Matrices Using Analytical Techniques - Kuber, B. Ramya (Asian Journal of Pharmaceutics (AJP), 2025)
Antimicrobial resistance (AMR) is an increasing global health challenge that reduces the effectiveness of existing treatments against a broad spectrum of pathogens. The current review outlines about the classification and spread of AMR, with a specific focus on multidrug-resistant (MDR), extensively drug-resistant (EDR), and pan-drug- resistant (PDR) organisms. MDR infections account for a significant number of deaths annually, with drug-resistant tuberculosis (TB) being a major contributor. EDR TB cases have shown a marked rise in recent years, particularly in certain geographic regions. PDR Gram-negative bacterial infections are linked to high mortality rates, posing serious treatment challenges. The growing presence of resistant fungal species and critical bacterial strains further highlights the complexity of the issue. Addressing AMR requires better monitoring, improved diagnostic methods, and the development of new antimicrobial strategies. Our study mainly focuses on the development and applications of various analytical techniques for the detection and analysis of resistant microorganisms from biological matrices, offering essential support for research and clinical practices.